Peripheral Monocytes Derived from Patients with Cystic Fibrosis and Healthy Donors Secrete NGAL in Response to Pseudomonas aeruginosa Infection. (August 2013) - Zughaier, Susu M.; Tangpricha, Vin; Leong, Traci; Stecenko, Arlene A.; McCarty, Nael A.
Background: Patients with cystic fibrosis (CF) develop chronic bacterial infections in the respiratory tract, reflecting dysfunctional innate immunity. Neutrophil gelatinase–associated lipocalin (NGAL) has 2 functions: one as an antibacterial host defense protein and the other as a physiological iron carrier. Neutrophil gelatinase–associated lipocalin (NGAL) has been validated as a biomarker for early kidney disease. The aim of this study was to determine whether NGAL could serve as a marker of acute pulmonary exacerbations in CF by measuring NGAL levels in serum samples from subjects with CF during stable clinic visits and during hospitalization for pulmonary exacerbations and comparing these levels to healthy controls and to patients without CF with significant infection. In addition, we aimed to determine if innate immunity cells other than neutrophils act as a source of NGAL. Methods: Circulating NGAL levels were measured by enzyme-linked immunosorbent assay in serum samples from 30 subjects with CF when hospitalized for an acute pulmonary exacerbation, 33 subjects with CF during stable clinic visits, 33 patients with sepsis, and 21 healthy controls. Secreted NGAL from CF and healthy control peripheral monocytes infected with Pseudomonas aeruginosa was also measured by enzyme-linked immunosorbent assay. Results: Serum NGAL levels were elevated in the patients with CF compared to the healthy controls ( P < 0.001). However, no difference in serum NGAL levels was found between subjects with CF with stable disease compared to subjects with CF undergoing pulmonary exacerbation. Furthermore, peripheral monocytes from CF and subjects without CF secreted NGAL upon infection with Pseudomonas aeruginosa and thereby may be contributing to the circulating NGAL levels observed. Conclusions: Our data show that peripheral monocytes secrete NGAL, and serum NGAL levels are widely distributed among subjects with CF, being elevated both when clinically stable and during a pulmonary exacerbation and thus NGAL is not a sensitive biomarker for pulmonary exacerbations.